Mental Health in Gen Z : How Self-Esteem, Fear of Missing Out, and Bullying Affect the Subjective Well-Being of High School Students - Dian Fitria (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2026)
Background: Adolescents’ today are part of Generation Z, growing up and living closely with digital life. This may potentially impact mental health and subjective well-being. Low self-esteem, fear of missing out (FoMO), and bullying may be important correlates of life satisfaction and affective states. Objectives:This study examined associations between mental health indicators, namely low self-esteem, FoMO, and bullying domains, and subjective well-being measured by life satisfaction, positive affect, and negative affect among adolescents. Methods: A cross-sectional survey was administered to 223 adolescents. Validated self-report instruments measured Rosenberg Self-Esteem Scale (RSES) , FoMo (fear of missing out scale), Revised Olweus Bully/Victim Questionnaire (OBVQ-R), and subjective well-being (Satisfaction with Life Scale, Positive Affect, Negative Affect). Descriptive statistics characterized the sample. Pearson correlation coefficients were computed to assess relationships among variables. Results:Participants were aged 17 to 19 years (M = 17.56, SD = 0.51). Most were female (60.5 percent). In terms of social media use, 33.6 percent reported three platform social media and 26.0 percent reported four platform social media. Correlation analyses indicated that lower self-esteem was associated with lower life satisfaction (r = .217, p < .01) and lower positive affect (r = .142, p < .05), and with higher negative affect (r = –.133, p < .05). Higher FoMO correlated with lower life satisfaction (r = –.146, p < .05) and higher negative affect (r = .235, p < .01). Total bullying scores were negatively correlated with life satisfaction (r = –.191, p < .01) and positive affect (r = –.159, p < .05), and positively correlated with negative affect (r = .177, p < .01). Conclusion:Low self-esteem, FoMO, and bullying are associated with poorer subjective well-being in adolescents. Targeted interventions addressing self-esteem and digital social dynamics may improve adolescent well-being Keywords: adolescents, bullying, fear of missing out, self-esteem, subjective well-bein